Effect of malnutrition at admission on length of hospital stay among adult surgical patients in Wolaita Sodo University Comprehensive Specialized Hospital, South Ethiopia: prospective cohort study - Gebregziabher, Zewdu; Nane, Debritu; Dake, Samson Kastro; Handiso, Yoseph Halala (Frontiers in Nutrition, 2024)
Background: Malnutrition in hospitalized patients remains a major public health problem in both developed and developing countries. Objective: This study was aimed to assess the prevalence of malnutrition at admission and its effect on length of hospital stay among adult surgical patients in Wolaita Sodo University Comprehensive Specialized Hospital, South Ethiopia, 2022. Methods: Study was conducted among 398 admitted surgical adult patients. Subjective global assessment was used to determine the nutritional status of patients with a minimum stay of 24 hours within 48 hours after admission(SGA). Data were collected by open data kit (ODK) version 2022.3.3 software while Stata version 14.1 software was employed for statistical analysis. Cox regression model was used to determine effect of malnutrition on the length of hospital stay (LOS) after adjusted for several potential confounders taken at admission. Adjusted Hazard ratio (HR) with 95% confidence interval was used to show the effect of malnutrition. Results: The prevalence of hospital malnutrition at admission was 64.32% (95% CI: 59%-69%) according to SGA classification. Adult surgical patients who were malnourished at admission had higher median LOS (12 days: 95% CI: 11-13) as compared to well-nourished patients (8 days: 95% CI: 8-9), means adult surgical patients who were malnourished at admission were at higher risk of reduced chance of discharge with improvement (prolonged LOS) (AHR: 0.37, 95% CI: 0.29-0.47) as compared to well-nourished patients. Presence of comorbidity (AHR: 0.68, 95% CI: 0.50-90), poly medication (AHR: 0.69, 95% CI: 0.55-0.86) and history of admission (AHR: 0.70, 95% CI: 0.55-0.87) within the previous five years were found to be the significant covariates of length of hospital stay (LOS). Conclusion: Magnitude of hospital malnutrition at admission was found to be high. Malnourished patients at admission had higher risk of prolonged length of hospital stay as compared to well -nourished patients. Presence of comorbidity, poly medication and history of admission were found to be the significant covariates of LOS. All stakeholders should give attention to reduce the magnitude of malnutrition and its covariates to improve the burden of LOS.